Size controlled synthesis of gold nanoparticles and sensor design. - Sim, Adeline Ching Ee. (2013)
Noble metal nanoparticles, such as AuNPs, have attracted tremendous interest due to their optical properties. Size and shape controlled synthesis of AuNPs act as a technological scaffold for practical studies, as properties of nanoparticles are prominently size and shape dependent. This has resulted in its widespread usage in a variety of applications, including cancer therapy, drug delivery or biosensors, which further raise the demands and needs on numerous shapes and size of AuNPs. Important progress has been made over the centuries on the synthesis and its sensitivity of nanoparticles.